Generation and detection of super small striations by F region HF heating. Issue 7 (31st July 2014) - Najmi, A.; Milikh, G.; Secan, J.; Chiang, K.; Psiaki, M.; Bernhardt, P.; Briczinski, S.; Siefring, C.; Chang, C.L.; Papadopoulos, K.
Abstract Recent theoretical models and preliminary observations indicate that super small striations (SSS) in the plasma density with scale size of 10 cm can be excited by F region HF heating at frequencies close to multiples of the electron gyrofrequency. We present here new experimental results using the High Frequency Active Auroral Research Program ionospheric heater at a frequency close to the fourth electron gyroharmonic with simultaneous GPS, Stimulated Electromagnetic Emission, ionosonde, and occasional Incoherent Radar Scattering diagnostics. Differential phase measurements of GPS signals through the heated region indicated the presence of SSS with extremely high amplitude (δn/n = 0.2–0.3) at scale size comparable to the electron gyroradius. The highest amplitude of GPS scintillations coincide with the highest level of the Broad Upshifted Maximum (BUM) and occurred when the HF frequency is slightly above the fourth harmonic of the electron cyclotron frequency. Frequency sweeps indicate that the scintillation amplitude exhibits hysteresis similar to that observed for the BUM amplitude when the HF frequency is cycled about the fourth harmonic of the cyclotron frequency. The results favor a four wave parametric process as the physical mechanism of the SSS. Additional experiments allowed the determination of the excitation and decay rates of the SSS.